Scandal and corruption in Congress - Pomante, Michael J., II (Emerald Publishing Limited, 2022)
Regardless of which political party Americans identify with, the sentiment that those who work in Washington are corrupt transcends partisanship. Since the breaking of the Watergate scandal, trust in the government has decreased significantly. While Congress did not engage in the Watergate break-in, the institution has still suffered the consequences, seeing citizens' distrust of politicians grow. However, Congress is not blameless, as it has had its share of scandal and corruption over the years. Scandal and Corruption in Congress guides readers through the history of corruption in Congress. Specifically, readers explore policies outlawing corruption, how Congress has attempted to hide unethical behaviour, getting caught, the repercussions of getting caught, and how corruption in the U.S. compares to corruption in other nations. Finally, to enlighten readers about the recent actions by Congress, several chapters address the impact of Citizens United and the #MeToo movement.